An Analysis of Intructional Planning Made by English Teacher of Eighth Grade Students at SMP Negeri 1 Ubud in the Implementation of Curriculum 2013 - ., Dwi Kadek Heryana; ., Drs.Gede Batan,MA; ., I Nyoman Pasek Hadi Saputra, S.Pd., M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
The curriculum reform in Indonesia gave a significant effect on the education system. Curriculum 2013 was the latest curriculum which implemented in most school in Indonesia. This curriculum required the teacher use the teaching and learning approach which stated in the curriculum itself. It was scientific approach which was becoming the approach in teaching, especially in teaching English. The recent study was aimed at finding out how relevant are the instructional planning made by English teacher of eighth grade students of SMP Negeri 1 Ubud in the implementation of Curriculum 2013, and what problems the teacher encountered in planning the instruction. This research found out that the instructional planning was relevant which gathered 96.4% percentage of the completeness of the components and the format. But, there was no relevancy of the teaching and learning activity with the learning methods used in scientific approach which include Discovery learning, Project-based learning, and Problem-based learning. Moreover, there were some problems encountered by the teacher in planning the instruction in teaching English. The problems were the teacher difficult to select and arrange the activity in scientific approach and the teacher difficult to create the assessment instrument. The findings of this research will be significantly contributed in determining whether or not the curriculum 2013 implemented regarding the current issues of the curriculum 2013 implementation problems. The result of this study will bring out some significant contributions on the development of the Indonesian education in general, the instructional planning in regard to the curriculum 2013 in particular. keyword : education, curriculum 2013, instructional planning, scientific approach